Second salvage high-dose-rate brachytherapy for radiorecurrent prostate cancer - Maenhout, Metha; Vulpen, Marco van; Moerland, Marinus; Peters, Max; Meijer, Richard; Bosch, Maurice van den; Nguyen, Paul; Frank, Steven; Zyp, Jochem van der Voort van (Journal of Contemporary Brachytherapy, 2017)
Purpose : Salvage treatments for localized radiorecurrent prostate cancer can be performed safely when a focal and image guided approach is used. Due to the low toxicity, the opportunity exists to investigate a second salvage treatment when a second locally recurrent prostate cancer occurs. Here, we describe a second salvage treatment procedure of 4 patients. Material and methods : Four patients with a pathologically proven second local recurrence were treated in an outpatient magnetic resonance imaging (MRI)-guided setting with a single fraction of 19 Gy focal high-dose-rate brachytherapy (HDR-BT). Delineation was performed using choline-PET-CT or a 68Ga-PSMA PET in combination with multiparametric 3 Tesla MRI in all four patients. Toxicity was measured using common toxicity criteria for adverse events (CTCAE) version 4.0. Results : With a median follow-up of 12 months (range, 6-15), there were 2 patients with biochemical recurrence as defined by the Phoenix-definition. There were no patients with grade 3 or more toxicity. In all second salvage HDR-BT treatments, the constraints for rectum, bladder, and urethra were met. Median treatment volume (GTV) was 4.8 cc (range, 1.9-6.6 cc). A median of 8 catheters (range, 6-9) were used, and the median dose to the treatment volume (GTV) was a D95: 19.3 Gy (SD 15.5-19.4 Gy). Conclusions : Second focal salvage MRI-guided HDR-BT for a select group of patients with a second locally recurrent prostate cancer is feasible. There was no grade 3 or more acute toxicity for these four patients.